Comparative Study of Compressive and Tensile Strength of Concrete Mixed with Steel and Glass Fibers - Bohora, Sangita; Awasthi, Keshab Datt; Bohara, Niraj (Journal of UTEC Engineering Management, 2025)
The mechanical characteristics of steel and glass fiber reinforced concrete, such as their compressive and tensile strengths, are reviewed in this work. Fibers are used to strengthen concrete and prevent cracking. In order to compare the best options for producing high-strength concrete, steel and glass fiber were used in a laboratory experiment with varying percentages of fiber blended in cube and cylindrical specimens. Glass fiber with a 150 aspect ratio and steel fiber corrugated with a 50 aspect ratio are used as additives at varied proportions of 0%, 0.5%, 1%, and 1.5% by weight of cement. For the M20 grade of concrete, a total of 63 cube specimens for 7, 14, and 28 days, as well as 21 cylinders for 28 days, were casted and tested in accordance with the Indian Standard (IS 516:1959) for compressive strength and (IS 5816:1999) for tensile strength. This study confirmed the beneficial effects of various fibers with a specific limit % increase in specimen compression improvement at 7, 14, and 28 days, as well as specimen splitting improvement at 28 days, by comparing the results of FRC with normal concrete. After 28 days, the maximum compressive strength of 24.39 N/mm2 and split tensile strength of 2.79 N/mm2 were achieved with a 0.5% glass fiber addition. After 28 days, the addition of 1% steel fiber resulted in a maximum compressive strength of 25.41 N/mm2 and a tensile strength of 3.18 N/mm2.